The Rationalization of Debt Discharge Policy for Individual Debtors in Indonesian Bankruptcy Regime - Robert Robert; Rosa Agustina; Bismar Nasution (Faculty of Law, Sriwijaya University, Indonesia, 2022)
The Indonesian bankruptcy regime tends to be harsh to the debtors, especially the individual debtors. In contrast, the creditors possess the right to pursue the debtor’s outstanding debts even after the bankruptcy process. For that reason, this article aims to argue why it is rational for the Indonesian government to implement a debt discharge policy in the Indonesian bankruptcy regime. This article employs a normative research method, using a conceptual and comparative approach. The result of this study is based on the debtor cooperation theory and the humanitarian theory of debt discharge. Hence, it is rational for the Indonesian government to implement a debt discharge policy for individual debtors. The first and second Sila of Pancasila is also in line with these theories. Consequently, as a member of society, the individual debtor should be treated with dignity and humane values, which includes debt forgiveness. Nevertheless, not every debtor is deserves to be discharged from his debts. Therefore, it is rational for the Indonesian government to implement the debt discharge policy in the amendment of Indonesian bankruptcy law to protect the honest but unfortunate individual debtors.